Science Forecasting & Detector Development for a High-frequency South Pole Telescope Camera ... - Dibert, Karia (University of Chicago, 2024)
I present a collection of forecasting, analysis, and instrumentation work related to the science cases and detector development for an upcoming camera for the 10-meter South Pole Telescope (SPT), called SPT-3G+. SPT-3G+ is a high-frequency, high-sensitivity camera designed to observe the cosmic microwave background (CMB) at 220, 285, and 345 GHz, targeting a variety of astrophysical and cosmological science cases. I first present forecasts of the expected sensitivity of SPT-3G+ to the recombination-era Rayleigh scattering of the CMB, a signal which probes the expansion and ionization history of the universe just after recombination, and whose first detection is sought by SPT-3G+. I find that, in combination with SPT-3G and Planck data, the expected detection significance is about 1.6-sigma, and that the cosmic infrared background, or CIB, is the major foreground inhibiting a higher detection significance. I next present an attempt to characterize the CIB using data from the 2019-2020 SPT-3G observing ...